2005
DOI: 10.1111/j.1467-6486.2005.00495.x
|View full text |Cite
|
Sign up to set email alerts
|

Generic Product Strategies for Emerging Market Exports into Triad Nation Markets: A Mimetic Isomorphism Approach

Abstract: Based on the concept of mimetic isomorphism, we theorize that, by imitating the home country MNE modal generic product strategy in each Triad nation, emerging market firms (EMFs) can improve their export performance satisfaction. We hypothesize that EMFs which: (1) target the EU and use a Premium strategy, (2) target Japan and use a Superior Value strategy, or (3) target the USA and use an Economy strategy will, on average, achieve higher levels of satisfaction with export performance than EMFs that enter emer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
107
1
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(112 citation statements)
references
References 51 publications
3
107
1
1
Order By: Relevance
“…Given IB's traditional focus on MNEs from developed economies, we currently know very little about how firms from emerging economies internationalize (such as how they overcome antidumping regimes erected as entry barriers) (Khanna & Palepu, 2006;Wright et al, 2005). If the field aspires to remain globally relevant, it seems imperative that more research be devoted to these crucial strategic issues (Brouthers et al, 2005;Dunning, 2006;Mathews, 2006;Narula, 2006).…”
Section: Future Research Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given IB's traditional focus on MNEs from developed economies, we currently know very little about how firms from emerging economies internationalize (such as how they overcome antidumping regimes erected as entry barriers) (Khanna & Palepu, 2006;Wright et al, 2005). If the field aspires to remain globally relevant, it seems imperative that more research be devoted to these crucial strategic issues (Brouthers et al, 2005;Dunning, 2006;Mathews, 2006;Narula, 2006).…”
Section: Future Research Directionsmentioning
confidence: 99%
“…This prediction has been refuted by the increasingly voluminous research that draws on the institutionbased view to tackle IB strategy problems in emerging economies. Five years later, in 2005, seven out of eight papers (88%) in the Journal of Management Studies special issue on strategy research in emerging economies, edited by two of the same editors as for the AMJ special issue and two new editors (Wright et al, 2005) (1) business groups (Chang & Hong, 2000;Guillen, 2000;Khanna & Palepu, 2000;Wan, 2005;Yiu, Bruton, & Lu, 2005); (2) privatization (Filatotchev, Buck, & Zhukov, 2000;Uhlenbruck & De Castro, 2000); (3) foreign investment strategies (Child & Tsai, 2005;Chung & Beamish, 2005;Delios & Henisz, 2000;Hitt et al, 2000;Isobe, Makino, & Montgomery, 2000;Meyer & Nguyen, 2005); (4) domestic strategies in emerging economies (Peng & Luo, 2000;White, 2000); and (5) internationalization strategies for firms based in emerging economies expanding abroad (Brouthers, O'Donnell, & Hadjimarcou, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The authors concluded that writing a business plan was symbolically done and offered internal value, but it did not lead to competitiveness. However, in another study, Brouthers, O'Donnell, and Hanjimarcou (2005) demonstrated that firms from emerging markets are able to improve their export performance satisfaction when they imitated the home country multinational enterprise (MNE) strategy in each triad nation. Emerging market firms are typically resource poor, and it is argued that they benefit from drawing on and leveraging the collective wisdom, experience, and resources of large firms.…”
Section: New Venture Performancementioning
confidence: 99%
“…They often begin operations as suppliers to other manufacturers or depend on third parties to distribute their products and lack requisite international experience compared with established firms in developed countries (Vernen-Wortzel and Wortzel 1988;Brouthers et al 2005). The Linkage, Leverage, Learning (LLL) framework suggested by (Mathews 2002(Mathews , 2006 explains how firms leverage prior linkages developed in the global economy through experiential learning and gain a foothold in the interconnected global network.…”
Section: Theoretical Underpinningsmentioning
confidence: 99%